Spectrophotometric Reaction Rate Method for the Determination of Ultra Trace Amounts of Vanadium(V) by its Catalytic Effect on the Oxidation of Naphthol Green B by Bromate in Micellar Medium - KEYVANFARD, MOHSEN (Asian Journal of Chemistry, 2010)
A simple, sensitive and selective catalytic spectrophotometric method was developed for the determination of ultra trace amounts of V(V).The method is based on the catalytic effect of vanadium(V) on the oxidation of Naphthol green B by bromate at acidic medium. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of Naphthol green B at 710 nm with a fixed-time method. The decrease in the absorbance of Naphthol green B is proportional to the concentration of V(V) in concentration range 0.10-40.0 ng/mL, with a fixed time of 0.5-4.0 min from initiation of the reaction.The limit of detection is 0.068 ng/mL V(V).The relative standard deviation of 10.0 and 40.0 ng/mL V(V) was 1.69 and 2.3 %, respectively. The method was applied to the determination of vanadium(V) in water.